A Researcher’s Journey from Traditional Qualitative Methods to Tech-Driven Insights - Khuan, Lee; Jamil, Nurul Akma; Muda, Siti Mariam (SOTVI - Society of Visual Informatics, 2024)
The integration of technology into qualitative research has revolutionised traditional methods, providing researchers with new opportunities and challenges. This paper compares the effectiveness, strengths, and limitations of traditional versus technology-based methods for recruiting participants, conducting interviews, and transcribing data, based on the personal experiences of the researchers. The findings reveal that while traditional face-to-face interviews enable deeper personal interaction and richer data collection, they are often time-consuming and logistically challenging. In contrast, technology-based methods offer increased accessibility, efficiency, and flexibility, particularly when recruiting participants and conducting interviews among geographically dispersed populations. However, these methods may compromise the depth of data due to the challenges of maintaining non-verbal cues and transcription accuracy, particularly when using automated transcription tools. This paper recommends a hybrid approach that combines the strengths of both methods. Best practices for using technology in qualitative research are proposed to ensure the richness and contextual depth of the data while leveraging the benefits of modern tools.